Complexity in valuation practice: an inquiry into valuers' perceptions of task complexity in the Dutch real estate market. Issue 3 (3rd July 2018) - Klamer, Pim; Bakker, Cok; Gruis, Vincent
ABSTRACT: The aim of this paper is to examine valuer judgement behaviour, by exploring the manifestation of task complexity in Dutch commercial valuation practice. For this purpose, we adopted a grounded theory approach and undertook 18 in-depth interviews with senior valuation professionals across the Netherlands. Our findings indicate a strong presence of situational task complexity in commercial valuation practice, as professionals operating in large valuation teams perceive different elements of task complexity throughout commercial valuation practice in comparison to peers working in small valuation teams or self-employed valuers. Further, coping strategies used to deal with task complexity vary substantially by type of valuer as well. From our data, we deducted three types of task environment constructs in which valuers operate, which basically represent the various levels of professional standards required by clients as well as organisational settings composed to meet client standards. As such, we found that task environment settings strongly coincide with perceptions of task complexity. The presence of situational task complexity in commercial real estate valuation practice points to the need for customisation of professional valuer's development programs to facilitate valuers to deal with task complexity in different stages of valuation practice and hence contribute to advancing valuer judgement skills.